ARCHAEOLOGICAL EXCAVATIONS IN THE BOSTAN BURIAL GROUND (KOGALINSKAYA VALLEY, ZHETYSU) IN 2023-2024 (Journal of history, 2025)
In 2023-2024, archaeological work was carried out on monuments located in the foothill area in the Kogaly valley of the Zhetysu region near the village of Bostan (Kerbulak district). Given the vastness of the Kogalinsky Valley, excavations of isolated burial mounds such as Bostan seem to be the most promising as they are informative in content. The main goals and objectives of the field work were: planned scientific work on the study of the cultural heritage site, protective archaeological excavations, clarifying the chronological framework of the monument's functioning, etc. During this period, 4 mounds were excavated in the valley, the uniqueness of which is manifested both in the funeral rite and in the material culture. The chronology of burial mounds has been established, a comparative analysis has been given, and both common features and their differences have been identified. The results obtained suggest that in the Early Iron Age there was a densely populated territory in which a confederation of tribes or a separate tribal structural unit could have lived. The presence of elite mounds, as well as small necropolises, clearly indicates the social differentiation of society. The study of the Bostan burial ground is an important step towards understanding the development of the Kogalinsky Valley in the Early Iron Age, and will also contribute to the development and development of new methods for studying the Saka culture.
Keywords: : Zhetysu; Kogaly; archeology; early Iron Age